Role of Technology in Agricultural Development - Shagufta (Journal of Commerce and Trade, 2018)
The economy of India is the seventh largest in the world by nominal GDP and the third largest by purchasing power parity the agriculture sector is main occupation in India’s economy but contributes to a declining share of its GDP, India ranks second worldwide in form output. New technologies are needed to push the field frontiers further, utilize inputs more efficiently and diversity to more sustainable and higher value cropping patterns. Indian agriculture has been changed the very face of this sector. The green revolution, blue revolution and yellow revolution and white revolution have been the important milestones in Indian agriculture. One thing common in all these revolutions was use of technology. The revolutions would not have accrued without relevant technologies.